2024
DOI: 10.1186/s40560-024-00717-3
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of permissive underfeeding for critically ill patients: an updated systematic review and trial sequential meta-analysis

Han-yang Yue,
Wei Peng,
Jun Zeng
et al.

Abstract: Background Our previous study in 2011 concluded that permissive underfeeding may improve outcomes in patients receiving parenteral nutrition therapy. This conclusion was tentative, given the small sample size. We conducted the present systematic review and trial sequential meta-analysis to update the status of permissive underfeeding in patients who were admitted to the intensive care unit (ICU). Methods Seven databases were searched: PubMed, Embas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 40 publications
0
0
0
Order By: Relevance
“…This observation is similar to the studies comparing different nutritional calorie or protein administration on the mortality. 8 , 9 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This observation is similar to the studies comparing different nutritional calorie or protein administration on the mortality. 8 , 9 …”
Section: Discussionmentioning
confidence: 99%
“… 8 Recent systematic review and meta-analysis evaluating the effect of permissive underfeeding vs standard feeding showed no difference in overall mortality. 9 Brazilian study on targets and prescription in the critically ill observed inadequacies in achieving nutrition targets, resulting in a negative nutritional balance. 10 A study done in the surgical ICU showed cumulative calorie and protein deficits were associated with prolonged ICU stay, fewer ventilator-free days, and increased complications.…”
Section: Introductionmentioning
confidence: 99%
“…A recent meta-analysis confirmed harm by early full feeding in critically ill patients as compared with permissive underfeeding. Although this meta-analysis did not include the EPaNIC RCT, it likely does not affect the conclusion, as EPaNIC patients were equally harmed by early full feeding [25]. A recent meta-analysis as part of the updated American feeding guidelines did not show benefit by supplemental parenteral nutrition as compared with enteral nutrition alone.…”
Section: Medical Nutrition Therapy In the Icu: Evidence From Rctsmentioning
confidence: 92%